VISIONARY LEADERSHIP STRATEGY OF THE SCHOOL PRINCIPLE IN IMPROVING THE QUALITY OF TEACHERS - Fathorrozi, Fathorrozi; Aisyah, Nur; Munif, Muhammad; Sugiono, Sugiono; Qodriyah, Khodijatul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study describes the strategy of visionary leadership in improving the quality of teachers at MTs Al Husna. Teacher quality is a very urgent thing to pay attention to, considering that teachers are actors in the learning process. Quality learning is obtained from quality teachers as well. This study uses a qualitative approach to the type of case study. The informants in this study consisted of four people, namely, the principal, deputy head of curriculum, deputy student affairs, and teacher. Data analysis goes through three stages, namely, data collection, data reduction, data display, and conclusions. The research results obtained are comparative studies, need assessment, training and supervision.